Arne B. Mann - Rómski kováči na Slovensku. Roma Blacksmiths in Slovakia: Bratislava: Ústredie ľudovej umeleckej výroby, 2018, 400 s., ISBN 978-80-89639-52-6 - Pechová, Jarmila (Romano džaniben, 2018)
RECENZE